KANDUNGAN PADA BUAH PARE SEBAGAI OBAT DIABETES MELITUS - Anak Agung Ayu Sauca Sunia Widyantari, Anak Agung Ayu Sauca Sunia Widyantari (UNHI Press, 2025)
The prevalence of degenerative diseases is increasing along with the increasing prosperity of society. Medicinal plants are proven to be one of the sources for raw materials for anti-diabetes mellitus drugs because among these plants have compounds that are efficacious as anti-diabetes mellitus. In this study, a literature approach or literature review method was used. Bitter melon plants are reported to contain secondary metabolites in the form of saponins, flavonoids, polyphenols, and beta carotene. These compounds are thought to stimulate the repair of beta cells so as to increase the process of insulin production. bitter melon fruit extract can increase the rate of cell metabolism through increasing and utilizing glucose by target cells whose effects are antidiabetic.